Using the properties of operations and the rules for multiplying and dividing, we can solve (9) ÷ (5-4) × (7-9) × (-5) ÷ (7-2) as follows:
First, we solve the expressions inside the parentheses:
(5-4) = 1
(7-9) = -2
(7-2) = 5
Next, we simplify the division operations:
(9) ÷ 1 = 9
-2 ÷ 5 = -0.4
Finally, we multiply all the results together:
9 × -2 × -5 × -0.4 = 72
Therefore, (9) ÷ (5-4) × (7-9) × (-5) ÷ (7-2) equals 72.
Use the properties of operations and rules for multiplying and dividing to solve (9)÷(5-4)×(7-9)×(-5)÷(7-2)
1 answer